Mencegah Paham Radikalisme Mahasiswa: Sebuah Model Pengembangan Kurikulum Berbasis Aswaja dan Kepesantrenan di Perguruan Tinggi - Mustajib; Miksan Ansori (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Radicalism among students poses a significant challenge to higher education institutions, as it undermines the development of a tolerant and moderate society. This study examines a curriculum development model based on Aswaja (Ahlussunnah wal jama’ah) and pesantren values at Institut Agama Islam Faqih Asy’ari (IAIFA) Kediri to counter radicalism and promote Islamic moderation. Utilizing a qualitative approach, this research analyzes the curriculum’s theoretical framework, management components, and implementation across six academic programs. The findings reveal that IAIFA Kediri integrates moderate Islamic teachings through subjects like Moderate Islamic Studies and Islamic classical texts (Kitab Kuning). Students are also immersed in pesantren environments that uphold tolerance and inclusivity. The curriculum model employs four perspectives: academic subjects, humanistic approaches, technological tools, and social reconstruction. This comprehensive design ensures the balance between academic excellence, personal growth, and social impact. The study concludes that pesantren-based curricula can effectively instill values of moderation and prevent the spread of radical ideologies. These findings contribute to the theoretical and practical development of Islamic education by offering a scalable model for other institutions facing similar challenges.